2020
DOI: 10.1007/s10570-020-03554-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and durability of contemporary unsized Xuan paper

Abstract: In China, Xuan paper has been the paper of choice as artwork support and for conservation, for several centuries. However, little is known about its material properties, especially given the many grades of sized and unsized Xuan paper. In addition, there is a lack of information on its degradation. In this research, a selection of contemporary unsized Xuan papers was investigated, representing diverse raw materials. Seven out of twelve contemporary unsized Xuan papers were determined to be approximately neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Further image processing was carried out in ImageJ software to determine the RGB values of the resultant color of each measurement. The obtained RGB values were transformed into grayscale intensity values through the weighted method, also called the luminosity method, in which each channel contribution is weighted according to its wavelength 35 . Moreover, to reduce any variations due to lighting conditions, RGB values from the background (zone of the pH strip that did not react with the sample) were transformed to grayscale intensity values in the same fashion, and then used to normalize the grayscale intensity values corresponding to each pH measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further image processing was carried out in ImageJ software to determine the RGB values of the resultant color of each measurement. The obtained RGB values were transformed into grayscale intensity values through the weighted method, also called the luminosity method, in which each channel contribution is weighted according to its wavelength 35 . Moreover, to reduce any variations due to lighting conditions, RGB values from the background (zone of the pH strip that did not react with the sample) were transformed to grayscale intensity values in the same fashion, and then used to normalize the grayscale intensity values corresponding to each pH measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Xuan paper is a traditional Chinese handmade paper usually used for Chinese calligraphy and painting, being the preferred paper for the conservation of paper-based artifacts. It is primarily composed of bark fibers of blue sandalwood (Pteroceltis tatarinowii), growing in calcium-rich soil, and rice straw (Oryza Sativa) growing in silica-rich soil 34 , 35 . Luo et al demonstrated that Xuan paper shows a similar temperature and light-induced degradation behavior as most western papers 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Different traditions and crafts explored various plant materials for papermaking through history both chronologically and geographically [1][2][3]. The variety of material and crafts process in East Asian countries makes papers that have different properties, such as Chinese Xuan paper [4,5], Japanese Washi [6,7] and Korean Hanji [8][9][10][11]. Among them, the Korean traditional handmade paper, commonly refers as Hanji, is a traditional symbol and heritage treasure from the Korean peninsula [10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional handmade paper, as an important carrier of inheriting human civilization, is featured excellent performance of its durability (Hubbe and Bowden 2009; Jeong et al 2014a,b; Luo et al 2019). It enjoys a great reputation as the king of paper that could last for more than 1000 years (Luo et al 2021;Tang et al 2017). Kaihua paper is a kind of legendary handmade paper in China, which was used exclusively by the imperial palace in the Qing Dynasty.…”
Section: Introductionmentioning
confidence: 99%
“…Although modern papermaking techniques have enhanced the production e ciency, the resultant loss of quality in handmade paper, especially long-term stability, calls for a united effort on this common decline. (Luo et al 2021;Baty et al 2010). Hence, it is of fundamental importance to understand the dynamic degradation of paper in multi-scale structures, and nd out how an accumulation of microscopic variation of cellulose structure results in the macroscopic deterioration of handmade paper involving discoloration and loss of mechanical resistance, which will enable ultimately access to preparing long-life handmade paper and possessing the great signi cance to the restoration of ancient books and cultural relics.…”
Section: Introductionmentioning
confidence: 99%